INFLUENCE OF VEGETATION COVER ON THE WATER QUALITY OF THE MANTARO BASIN, PERÚ - Zambrano Delgadillo, Katheryne Priscilla (2024)
This research determined the influence of vegetation cover, through the NDVI, on water quality in the Mantaro basin, using 27 monitoring points of category 3, established by the ANA. Thirteen parameters were considered: BOD5, COD, DO, TC, pH, As, Al, Mn, Fe, Cd, Pb, B, and Cu. The NDVI data were downloaded from the MOD13Q1 V6.1 product available in Google Earth Engine. The analysis revealed that the temporal behavior of the water quality parameters varies by season, with maximum values recorded in summer and minimum values in winter for all physicochemical and organic parameters in the Upper and Lower Mantaro basins. In the Middle basin, the maximum values for TC, BOD5, and COD were recorded in winter and spring. Strong positive and negative correlations (pvalue <0.05) were obtained between the NDVI and the water quality parameters, primarily in winter. The results suggest that NDVI is a potential indicator for analyzingwater quality, useful for the implementation of predictive models